Indonesian Media Framing of Reportage on the Crimean Peninsula Crisis - Mochamad Aviandy; Shuri Mariasih Gietty Tambunan; Silva Tenrisara Pertiwi Isma (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This research investigates how one of the mainstream media in Indonesia frames Russia in its reportage. One of the selected cases is the 2014 Crimean Peninsula crisis. The Crimean Peninsula Crisis was a major international event that reported comprehensively by Kompas. This research will reveal Kompas’ bias in its reportage on Crimea and the factors that underlie the bias. In investigating the issue, this research uses Norman Fairclough’s critical discourse analysis. It follows Fairclough method of critical discourse analysis by using text as a discourse. It is found that as one of the mainstream media in Indonesia, Kompas reportage is not neutral as it depicts Russia through a negative frame. Analysis on semiotic factors, intertextuality, and how the media bias could be handled are the focuses of this research.